Analisis Komparatif Tingkat Kesehatan Bank Syariah Indonesia dan Bank BUMN Konvensional Berdasarkan Metode RGEC - Rizkia Ramadhani; Irma Andriani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to assess and compare the financial health of Bank Syariah Indonesia (BSI) with state-owned conventional banks, namely Bank Mandiri, BNI, BRI, and BTN, using the Risk Profile, Good Corporate Governance, Earnings, and Capital (RGEC) method. The research employs a quantitative approach with a descriptive comparative method. Secondary data were collected from the financial statements of each bank for the period 2021 to 2024. The results of the analysis show that all banks fall within the healthy to very healthy categories. BSI, BRI, Bank Mandiri, and BNI obtained a composite rating of 1 with a very healthy classification, while BTN received a composite rating of 2 with a healthy classification. These findings indicate that BSI, as the only state-owned Islamic bank, is able to compete effectively and demonstrates performance that is comparable to, and in some aspects superior to, that of conventional state-owned banks.